Economic Development of Communities with Sustainable Living Approach in Block A Ex-Million-Hectare Land Project in Mangkatip Village - Nasir, Darmae; Wisman, Yossita; Hidayat, Nasrullah (JURNAL GEOGRAFI, 2024)
This type of research is Participatory Rural Appraisal (PRA) method research, namely planning, observing, implementing and evaluating activities together in empowerment activities. Data collection techniques were collected using questionnaires and interviews from the community. This research shows that a sustainable livelihood development program in the context of community economic development on a rural scale needs to be carried out, as is the case with Mangkatip Village, a village located in the Ex-Peatland Project Area (PLG). The people's economy in Mengkatip Village is still based on agriculture and is highly dependent on natural resources. A community economic development approach with a sustainable livelihood approach can be implemented in household economic development in a Mengkatip village. Developing a household economy based on a sustainable livelihood approach is a responsible way to maintain ecological and social balance. The Million Hectare Land Project is a project that is considered to cause various environmental problems. Not only about the physical environment but also about society and the humanities. To address this, a sustainable approach has been taken. Therefore, planning for economic empowerment through sustainable resource development is very important in areas experiencing environmental degradation.Keywords: Development; Social Economy; Sustainable.